Transformacja systemu politycznego Chin w czasach późnego cesarstwa (1368-1911) - Niewiński, Stanisław (Katedra Doktryn Politycznych i Prawnych Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2022)
During the late imperial era, China was ruled by two dynasties: the Ming (1368-1644) and the Qing (1644-1912). The state then underwent a transformation in a more autocratic direction. The position of the emperor was strengthened. The bureaucratic apparatus was subordinated to the monarch. The state also became more repressive towards its people.
Keywords: China; empire; autoritarism; emperor; bureaucracy